ON GRAMMATICAL FEATURES OF FOLK SONG LANGUAGE - Nejedlý, Petr (Bohemica Olomucensia, 2021)
The article deals with the language of folk songs. It analyses three ones from the oldest song collections from the turn of the 18th and 19th centuries (Antonín Francl, Václav Hanka sr., Jan Jeník, knight of Bratřice) untouched by romanticising interferences of editors. Folk song belongs to the non-artificial art and its language shows features of the functional style that uses means from various language structures and, above all, it is not identical with a dialect. It is especially evident at lowest language plans. The author characterises the repertory of grammatical means of folk song as an open system: this attribute corresponds with the main features of folklore: oral transmission, the identity of the production and reproduction, the anonymity of the author, the absence of the proto-text, variability, and unstable boundaries of texts.
Keywords: Czech folk song; Antonín Francl; Václav Hanka sr.; Jan Jeník; knight of Bratřice; language; grammatical features